Agroecologia e antropologia pubblica nelle Terre Alte: comunità, margini, saperi trasversali - Villa, Marta (Antropologia Pubblica, 2024)
The article documents the applied anthropological research carried out within the European project ECOVINEGOALS. The field of investigation area was the Val di Cembra, a marginal area of the High Lands in the Autonomous Province of Trento (Italy), which also has different forms of land tenure, including commons. The project was structured to promote a new agricultural vision in the vineyard of quote: interdisciplinary research was carried out (agronomists, geographers, economists, anthropologists). The key to the reflection was the landscape and the younger generations: through a series of dialogues between different stakeholders and participatory meetings involving the community of Valle di Cembra, the possibility of introducing agroecological theories and practices in the vineyard was considered and an effective exchange of expertise between generations was implemented. The main objectives of the project were those set out in the EU Biodiversity Strategy for 2030 and the European Green Deal. The activation of specific practices of public anthropology has allowed the emergence of bottom-up participatory strategies resulting from inter-generational dialogue and reflection. Finally, specific action plans were adopted with the community to mitigate the crisis in the agricultural sector of the highlands in relation to climate crisis. In fact, the action plans aim at establishing a mechanism for the regeneration of the territory and the social fabric, starting from a a major investment in the field of permanent and dialogical training.